Characterization of bacterial isolates from skin lesions of sheep, goat and cattle in different rearing condition - Saha, Tapu Kumar; Begum, Ferdousi; Kabir, S M Lutful; Islam, Md Shafiqul; Khan, Md Shahidur Rahman (Asian Journal of Medical and Biological Research, 2019)
The study was performed to isolate and characterize some selected bacteria from skin lesion of sheep, goat and cattle of different rearing condition. Intensive and semi-intensive housing systems were considered for this study. A total of (n=60) skin wound swab and pus samples were collected for this study during the study period. Among them (n=30) samples were collected from intensive farms and (n=30) samples were collected from semi-intensive farms. Staphylococcus aureus infections were found 70% skin lesion for sheep, 30% for goat and 60% for cattle and Pseudomonas aeruginosa infections were found 5% skin lesion for sheep, 15% for goat and 15% for cattle. Semi-intensive farm animals were more infected by bacteria than intensive farm animals. Staphylococcus aureus affected 53.33% in intensive farm animal and 66.67% in semi-intensive farm animal. Pseudomonas aeruginosa affected 10% animal in intensive housing system and 13.33% in semi-intensive housing system. The organisms were isolated and characterized by morphological, cultural and biochemical characteristics and identified by polymerase chain reaction. Staphylococcus aureus produced yellowish colony in nutrient agar and golden yellow colony in mannitol salt agar. Positive isolates were produced β–hemolysis in blood agar. Pseudomonas aeruginosa produced characteristic colony in nutrient agar but not produce pigment. Pseudomonas aeruginosa produced colorless colony in MaCconkey agar, violet colony in EMB agar and produced hemolysis in blood agar. Staphylococcus aureus showed Gram positive, cocci shaped and grapes like arrangement and Pseudomonas aeruginosa showed Gram negative, short rod shaped. Staphylococcus aureus fermented five basic sugars and produced gas and Pseudomonas aeruginosa fermented dextrose and mannitol. Both organisms were catalase positive, only Pseudomonas aeruginosa was oxidase positive. Pseudomonas aeruginosa isolates were further characterized by PCR amplification of toxA gene primer. Staphylococcus aureus skin infection treatment was noticed more effective by erythromycin and gentamicin and Pseudomonas aeruginosa skin infection treatment more effective by ciprofloxacin and gentamicin. Both the organisms were found to be amoxicillin resistant. This is the first and preliminary report of molecular characterization of Pseudomonas aeruginosa from skin lesion of sheep, goat and cattle associated with a different rearing condition of the animals in Bangladesh. Asian J. Med. Biol. Res. June 2019, 5(2): 117-125